The Effect of Entrepreneurial values and Self-Confidence on Entrepreneurial Interest in Elementary School Student - Citra Nur Anisa; Alpin Alghani; Achmad Syarifudin (MIREJ: Multidisciplinary Innovation Research Journal, 2026)
Previous research This study was to understand the relationship between the three components of Planned Behavior Theory and the mediating effect of these components on the relationship between Entrepreneurship education and Self-efficacy on Entrepreneurial intentions among experienced students in Vietnam. The findings show that Entrepreneurship education has a direct positive effect on attitudes towards entrepreneurship, control of perceived behavior and subjective norms Entrepreneurship of engineering students in Vietnam. These findings are consistent with many previous studies have confirmed the role of entrepreneurship education in shaping students' entrepreneurial intentions. The main goal of this approach is to obtain empirical data that can be used in testing theoretical models through statistical analysis. Based on the results show that entrepreneurial self confidence (ESC), significantly mediated the relationship between Entrepreneurial Value (EV) and Entrepreneurial Interest (EI). Entrepreneurial values (EV) and Entrepreneurial Interests (EI) significantly mediates the relationship between entrepreneurial self confidence (ESC) and entrepreneurial interest (EI). The values that individuals believe in relation to the world of entrepreneurship strengthen their intention to become entrepreneurs. A number of studies have shown that entrepreneurship education at the elementary level can play an important role in shaping students' attitudes and interests in entrepreneurship in the future.